The effect of progressive muscle relaxation using biofeedback therapy on engineering and technical students - Norizan, Yusof; Abdul Rashid, Abdul Aziz; Sawai, Rezki Perdani (Kaizentrenovation Sdn Bhd, 2021)
The transition process facing by the students from secondary school to an engineering and technical institute of higher learning contributes to the challenges in emotional, social and academic aspects. At the same time, the changes in the environment of educational setting also gives a huge impact towards physiological status of the students. Students may expose to an increase in physiological arousal state which further affect student’s psychology and performance in university. Until now, there is no special program or module in counselling session that can help in reducing the physiological arousal among engineering and technical student. Therefore, this study aims to develop and evaluate the effectiveness of progressive muscle relaxation with spirituality element using a biofeedback therapy in lowering physiological arousal of the students. This is an experimental quantitative study involving 54 technical students with disciplinary problems. DASS Questionnaire was used in determining the psychological state of the subjects. They are divided into two group which are treatment and control group in 4 session using progressive muscle relaxation with spirituality element for treatment. Another group is a control groups which received the progressive muscle relaxation without spirituality elements. Both groups are required to undergo biofeedback test before and after training. The result revealed that both progressive muscle relaxation with spirituality elements using biofeedback therapy is more effective in lowering psychological arousal as compared to the progressive muscle relaxation without spirituality elements. Indeed, the findings from this study provide a new effective technique that can be applied in counselling sessions as an empowerment to the existing counseling technique in helping the clients.